Spectrophotometric and enzymatic methods for biochemical analysis of blood sera from farm animals - D. S. Bolshakov; T. B. Nikeshina (Ветеринария сегодня)
Conventional and present-day principles of spectrophotometric and enzymatic determination of major biochemical values of animal blood serum (plasma) are described in the paper: total protein, albumin, urea, uric acid, creatinine, bilirubin (total and conjugated bilirubin), glucose, lactic acid, triglycerides, Cholesterine, phospholipids, calcium, magnesium, phosphorus, potassium, sodium, ferrum, chlorides, alkaline phosphatase, lactate dehydrogenase, creatine kinase, a-amylase, aspartate aminotransferase, alanine aminotransferase, Cholinesterase, γ-glutamyltransferase and hemoglobin.